Factor Structure of the Teacher Reflection Scale for Primary and Secondary School Teachers - Vukanović, Nemanja D.; Skopljak, Margareta G.; Mihajlović, Tatjana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Reflection represents a key element for professional development and the transformation of teachers’ knowledge and practice. It is a complex, multidimensional process that encompasses various aspects of teachers’ professional activities. The aim of our research was to determine the factor structure of the reflection scale on a sample of 423 teachers—268 primary school teachers and 155 secondary school teachers from Banja Luka. The research instrument applied was the Teaching Reflection Inventory (TRI). To determine the factor structure of the scale, several analyses were conducted, including descriptive statistics, the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy, Bartlett’s test of sphericity, communalities for each variable, Cattell’s scree test, the initial component matrix, the rotated component matrix, and the component transformation matrix. Four factors with satisfactory internal consistency were extracted: affective (α = 0.903), cognitive (α = 0.838), metacognitive (α = 0.843), and practical aspect (α = 0.743). The obtained results indicate that the applied instrument is valid for measuring teachers’ reflection and that it can serve as a tool for teachers’ professional development. Given the sample size, it would be desirable to conduct a comparative analysis of the TRI instrument in multiple countries for cross-cultural validation, as well as to conduct longitudinal research to track the development of teachers’ reflective practices.